ANALISIS MAXIMUM SUSTAINABLE YIELD (MSY) SUMBER DAYA CUMI-CUMI (LOLIGO SPP.) DENGAN PENDEKATAN BIOEKONOMI DI TEMPAT PELELANGAN IKAN PELABUHAN MUARA ANGKE - Wibowo, Aldhy
Fish Auction Place (TPI) Muara Angke is a fish shelter located in Muara Angke, North Jakarta. The highest fishery resource commodity that landed at the TPI Muara Angke was squid (Loligo spp.). Squid is one of marine fishery resources in Indonesia that has economic value because it has high nutritional and protein content. High market demand for squid in Indonesia makes squid prices tend to rise every year. This study aims to determine the level of production, fishing effort, and utilization rate with biotechnical and bioeconomic approaches so that the management of squid resources can be carried out in a sustainable manner. The method that used in this research is biotechnical analysis and bioeconomic analysis. The results of the estimation of squid biological parameters showed an intrinsic growth rate (r) of 1.33 tons/year, a fishing gear coefficient value (q) of 0.0006 tons, and an environmental carrying capacity (k) of 3.21 tons/year. year. The maximum catch limit of squid (MSY) is 22,418,604 kg, while in 2018 the actual catch of squid is 24,057,542 kg, so that the effort to catch squid by Muara Angke fisherman in 2018 has exceeded the Maximum Sustainable Yield limit. (MSY). In addition, the utilization of squid resources has reached 116%, so it can be concluded that the fishing effort by the fisherman of Muara Angke Port is categorized as overfishing that can threat the sustainability of fish resources in a sustainable manner.